2016
DOI: 10.1177/0272431616678988
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Implications of Social Avoidance in Chinese Early Adolescents

Abstract: The goals of the present study were to (a) develop and validate a new self-report measure of social avoidance for use among early adolescents in mainland China and (b) explore the links between subtypes of social withdrawal (i.e., shyness, unsociability, and social avoidance) and indices of socio-emotional difficulties in this cultural context. Participants were 663 early adolescents (350 boys, 313 girls) attending elementary schools ([Formula: see text] = 10.25 years) and middle schools ([Formula: see text] =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
58
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 52 publications
(126 reference statements)
6
58
1
Order By: Relevance
“…Results provide initial support for the notion that social avoidance is a particularly maladaptive form of social withdrawal. For example, socially avoidant older children reported higher social anxiety than unsociable and non‐withdrawn children (Coplan et al, ), and social avoidance in Chinese children was uniquely associated with indices of both peer and internalizing problems (Sang et al, ). Socially avoidant young adults also reported more emotional dysregulation and relationship difficulties than did unsociable or non‐withdrawn individuals (but did not differ significantly from their shy counterparts) (Nelson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Results provide initial support for the notion that social avoidance is a particularly maladaptive form of social withdrawal. For example, socially avoidant older children reported higher social anxiety than unsociable and non‐withdrawn children (Coplan et al, ), and social avoidance in Chinese children was uniquely associated with indices of both peer and internalizing problems (Sang et al, ). Socially avoidant young adults also reported more emotional dysregulation and relationship difficulties than did unsociable or non‐withdrawn individuals (but did not differ significantly from their shy counterparts) (Nelson, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a factor that may have been confounded with cultural context is the informant of unsociability. Beyond early childhood, studies of unsociability in Western cultures have often used self‐report whereas studies in China have predominately relied on peers’ report until recent years (e.g., Coplan et al, ; Liu, Zhou, Li, & Chen, ; Sang et al, ). However, cross‐informants’ (self vs. peer) agreement on unsociability still rarely has been examined, especially in China.…”
Section: Introductionmentioning
confidence: 99%
“…The items capture a combination of an overt preference for solitude (rather play alone than with others), a lack of social interest (not interested in group activities), and also a dislike of social interactions (‘does not prefer social interactions’ and ‘would not like to talk with others’; e.g., Chen et al, ; Ding et al, ; Liu et al, ). Despite the historical reliance on peer nominations in social withdrawal research in China, self‐reported unsociability has emerged in recent years and been increasingly used (e.g., Coplan et al, ; Liu, Zhou, et al, ; Sang et al, ). In these studies, unsociability assessed with the adapted Child Social Preference Questionnaire (Coplan et al, ) demonstrated good internal consistency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations